Оцінка мотивації щодо вибору майбутньої професії студентами - старшокурсниками медичного вузу - Ярцева, Марія Олександрівна; Гиря, Олена Максимівна; Yartseva, M.; Hyria, O. (My University, 2018)
У статті проаналізовано анкети студентів-старшокурсників медичного університету, які висвітлюють мотиваційні характеристики студентів щодо вибору майбутньої професії. Встановлені основні чинники, що вплинули на вибір професії та вищого навчального закладу, означені найбільш перспективні, на погляд студентів, напрямки в медицині, визначені подальші наміри випускників медичного вишу щодо працевлаштування. The article analyzes the questionnaires of undergraduate students of the medical university, which highlight the motivational characteristics of students in choosing a future profession. The main factors influencing the choice of profession and institution of higher education were identified, the most promising, in the eyes of the students, directions in medicine were identified, and the further intentions of graduates of the medical college regarding employment were identified.
Evaluation of motivation for the selection of future profession of last-year students of medical high school
Keywords: мотивація; студенти; медичний університет; вибір; професія; motivation; students; medical university; choice; profession